Transgender people and criminal justice: an examination of issues in victimology, policing, sentencing, and prisons - Panter, Heather; Dwyer, Angela (Critical Criminological Perspectives, 2023)
This cutting-edge book examines the unique issues that transgender identities face globally in the criminal processing system through empirical and theoretical contributions. The contributing authors range from established transgender scholars, transgender equality rights activists, transgender policy influencers, researchers from non-profit groups, and former criminal justice practitioners. The book covers many under-developed issues for transgender identities like criminalization, victimization, court experiences, law enforcement and the policing of gender, the school to prison pipeline, and incarceration. It provides a significant advancement in queer criminology and trans studies globally. Heather Panter is Senior Lecturer/ Programme Leader at Liverpool John Moores University, UK, and a retired American police detective with 13+ years of law enforcement experience with local and federal police agencies. Her previous academic research involved the comparative cross-examination of policing within the United States and the United Kingdom in respect to officers’ cognitive and social perceptions of LGBT+ identities. Angela Dwyer is Associate Professor in Policing and Emergency Management in the School of Social Science at the University of Tasmania and the Deputy Director of the Tasmanian Institute of Law Enforcement Studies. She is the founding Co-Chair of the Division of Queer Criminology with the American Society of Criminology and conducts research around the frontline policing experiences of LGBTIQ people.